1989
DOI: 10.1128/iai.57.3.932-936.1989
|View full text |Cite
|
Sign up to set email alerts
|

Experimental cecitis in gnotobiotic quails monoassociated with Clostridium butyricum strains isolated from patients with neonatal necrotizing enterocolitis and from healthy newborns

Abstract: Using axenic quails fed a diet containing lactose, we have investigated the potentially pathogenic roles of six Clostridium butyricum strains of human origin. Three strains (CB155-3, CB1002, and CB203-1) isolated from neonatal necrotizing enterocolitis patients and two of three strains (CB19-1 and CB25-2) isolated from healthy newborns led to cecal or crop lesions or both similar to those observed in human neonatal necrotizing enterocolitis: thickening of the cecal wall with gas cysts, hemorrhagic ulcerations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 22 publications
1
17
0
1
Order By: Relevance
“…butyricum were found in healthy human newborn babies (Gothefors and Blenkharn 1978;Smith et al 1980;Fontaine et al 1986), a number of studies have suggested that this species has a potentially deleterious effect in alactasic premature babies, because fermentation of undigested lactose leads to excessive production of H, and butyrate. These two metabolites have been associated with the occurrence of neonatal necrotizing enterocolitis (Popoff et al 1985;Bousseboua et al 1989). In our model of trixenic rats, clostridial counts remained high, but participation of this organism in GOS degradation appears doubtful because fermentation products associated with glycolytic activity of CI.…”
Section: Discussionmentioning
confidence: 99%
“…butyricum were found in healthy human newborn babies (Gothefors and Blenkharn 1978;Smith et al 1980;Fontaine et al 1986), a number of studies have suggested that this species has a potentially deleterious effect in alactasic premature babies, because fermentation of undigested lactose leads to excessive production of H, and butyrate. These two metabolites have been associated with the occurrence of neonatal necrotizing enterocolitis (Popoff et al 1985;Bousseboua et al 1989). In our model of trixenic rats, clostridial counts remained high, but participation of this organism in GOS degradation appears doubtful because fermentation products associated with glycolytic activity of CI.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Bousseboua et al showed that lactose fermentation was a prerequisite for the expression of C. butyricum enteropathogenicity. Numerous gas cysts were always observed in the caecal wall of quails mono-associated with C. butyricum [50]. Neuraminidase production has also been described as a major virulence factor in C. butyricum strains causing NEC in preterm neonates [51].…”
Section: Necmentioning
confidence: 99%
“…High production of SCFAs associated with abnormal C 4 ratio (above 40%) has previously been demonstrated as potentially deleterious in infants 5 as in experimental models. 39,40 Therefore, factors responsible for the increase in butyric acid need to be explored. SCFA concentrations and profiles found during this study are in accordance with our previous study in preterm infants when their gestational age varied from 30 to 36 weeks.…”
Section: January-february 2002mentioning
confidence: 99%